Pola Konsumsi Masyarakat Miskin di Kecamatan Pangkalan Kuras Kabupaten Pelalawan Provinsi Riau - Sartini Sartini; surtani surtani; Fitriana Syahar (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
ABSTRACT This research aimed to determine consumption patterns of the poor people in Pangkalan Kuras Subdistrict, Pelalawan Regency, Riau Province. The type of this research is descriptive with quantitative approach. The population in this research are all poor families who live in Pangkalan Kuras subdistrict are which amounted to 2.558 families. The sample was determined using the Slovin formula so that obtained to 97 families. The result showed that the food consumption patterns of the poor people in Pangkalan Kuras sub-district larger than the consumption pattern of non food..proportion to the pattern of food consumption is 55.37% or Rp 1,520,370, while the consumption pattern of non food is 44.63% or Rp 1,225,492. Keywords : consumption patterns, poor people, food consumption